ANALISIS CONTAGION EFFECT PANDEMI COVID – 19 TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR OTOMOTIF DAN KOMPONEN YANG LISTED DI BURSA EFEK INDONESIA - Prasetyo, Febri; Diyah Probowulan,; Astrid Maharani, (Juremi: Jurnal Riset Ekonomi, 2021)
This study has the objective of investigating the changes in the Contagion Effect on stock prices before and after the Covid-19 pandemic in manufacturing companies recorded on the Indonesia Stock Exchange. The object of the study includes 10 companies in the automotive and component sub-sector manufacturing companies. This research is classified as descriptive according to quantitative data. In addition, external data was used, and secondary data was employed as the data source. Moreover, library research, field research, and also internet research were used as the techniques of data collection. Then, the technique of analyzing the data implemented descriptive statistical analysis along with associative analysis. According to the research results, significant difference could not be seen in share prices both, before or after the declaration of the earliest Covid-19 case in Indonesia in Automotive and Component Sub Sector Manufacturing companies recorded on the Indonesia Stock Exchange.